The role of the fibroblast growth factor family in bone‐related diseases. (4th August 2019) - Wang, Jicheng; Liu, Shizhang; Li, Jingyuan; Yi, Zhi
Abstract: Fibroblast growth factor (FGF) family members are important regulators of cell growth, proliferation, differentiation, and regeneration. The abnormal expression of certain FGF family members can cause skeletal diseases, including achondroplasia, craniosynostosis syndrome, osteoarthritis, and Kashin–Beck disease. Accumulating evidence shows that FGFs play a crucial role in the growth and proliferation of bone and in the pathogenesis of certain bone‐related diseases. Here, we review the involvement of FGFs in bone‐related processes and diseases; FGF1 in the differentiation of human bone marrow mesenchymal stem cells and fracture repair; FGF2, FGF9, and FGF18 in osteoarthritis; FGF6 in bone and muscle injury; FGF8 in osteoarthritis and Kashin–Beck disease; and FGF21 and FGF23 on bone regulation. These findings indicate that FGFs are targets for novel therapeutic interventions for bone‐related diseases. Abstract : Here, we review the biological relevance of FGF1, FGF2, FGF9, FGF18, FGF6, FGF8, FGF21, and FGF23 in bone‐related diseases. These findings potentiate the targeting of FGFs family members for novel therapeutic interventions in bone‐related diseases and may also hold valuable clinical potential to improve the care of patients with bone‐related diseases.